2020
DOI: 10.1007/s10620-020-06499-6
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Chronic Viral Hepatitis and Liver Fibrosis Among Mongols in Southern California

Abstract: Background: Mongolia is a highly endemic region for chronic hepatitis B (HBV), hepatitis delta (HDV), and hepatitis C (HCV) infections. Aim of this study was to comprehensively characterize chronic viral hepatitis among Mongols living in Southern California. Methods: Three screening events were conducted between August to November 2018, with 528 adult Mongols tested for HBV and HCV. HBsAg (+) individuals (CHB) underwent additional testing for HDV RNA and anti-HDV. Liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Our findings are similar to existing studies in smaller US cohorts reporting low rates of HDV testing among CHB patients (4,10–12). Gish et al (12) retrospectively evaluated 1191 CHB patients at a single center from 2002 to 2007 and observed that 499 patients underwent HDV testing, among whom 42 (8%) were found to be HDV-positive.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are similar to existing studies in smaller US cohorts reporting low rates of HDV testing among CHB patients (4,10–12). Gish et al (12) retrospectively evaluated 1191 CHB patients at a single center from 2002 to 2007 and observed that 499 patients underwent HDV testing, among whom 42 (8%) were found to be HDV-positive.…”
Section: Discussionsupporting
confidence: 91%
“…36 As in Europe, the infection predominates in IVDUs and foreign-born individuals. [37][38][39][40] Although the scarcity of HBsAg carriers in the US may affect perceptions on the impact of CHD, the recent NHANES findings would support screening all HBsAg carriers.…”
Section: Hdv Infection In Europe and The Usmentioning
confidence: 99%
“…The "at risk" groups include persons who inject illicit drugs, persons with HIV, men who have sex with men, those at risk for sexually transmitted diseases, and persons who emigrated from countries of high endemicity [8]. The importance of country of origin as a risk factor for HDV in the USA is underscored by the study from Fong and colleagues from the University of Southern California published in this issue of Digestive Diseases and Sciences [9]. Among 534 Mongol immigrants and their families who participated in three community screening events conducted in 2018, 9.7% were HBsAg positive, and among these individuals, 41% were anti-HDV positive, one-third of whom were HDV RNA positive.…”
mentioning
confidence: 99%